The Role of Context in Directing Quranic Readings: Analyzing Discourse Transition and Its Impact on Interpretation: دور السياق في توجيه قراءات القرآن الكريم: تحليل انتقال الخطاب وتأثيره على التفسير - Ali Ali Hussein Ghazwan (Walidem Institute and Publishing (WIP), 2025)
Objective: The objective of this study is to explore the role of context in directing Quranic readings, particularly in light of the transition of verbal discourse, by linking verbs to their preceding and succeeding contexts. It aims to define context, explain the guidance of Quranic readings, and analyze discourse transition. Theoretical Framework: This research is based on the hermeneutics of the Qur’an, particularly the contextual approach in interpretation. This theory emphasizes that the meaning of the Qur’an depends not only on the text but also on its linguistic and historical context. Literature Review: The literature review discusses previous studies on contextual interpretation in Quranic readings, highlighting the contributions of classical and modern scholars. Methods: The study employs a descriptive, analytical, and contextual approach as its methodology, analyzing different types of verbal discourse transitions in Quranic readings and providing examples that illustrate their contextual significance. Results: The results indicate that scholars guiding Quranic readings prioritize interpretations that align with the context, considering them stronger and more appropriate than alternative readings. Context is categorized into internal linguistic context and external situational context, both of which play a comprehensive role in directing Quranic readings. Implications: This research enriches the methodology of Qur’anic interpretation by emphasizing the role of context in understanding discourse transitions, helping scholars, religious leaders, and society interpret verses more accurately and relevantly. Novelty: The novelty of this study lies in its focused exploration of the role of discourse transition in contextualizing Quranic readings, an area that has not been extensively examined in previous research.